2008
DOI: 10.1186/1479-5868-5-40
|View full text |Cite
|
Sign up to set email alerts
|

Perceived sports competence mediates the relationship between childhood motor skill proficiency and adolescent physical activity and fitness: a longitudinal assessment

Abstract: Background: The purpose of this paper was to investigate whether perceived sports competence mediates the relationship between childhood motor skill proficiency and subsequent adolescent physical activity and fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
313
3
26

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(368 citation statements)
references
References 59 publications
26
313
3
26
Order By: Relevance
“…The SPPC is a highly reliable (internal consistency reliability of 0.71 ≤ r ≤ 0.91 for the different subscales) and valid instrument to assess different dimensions of self-perception among third-till eighth-grade pupils (aged 8-13 years, Harter, 2012). Similar to previous studies (e.g., Barnett et al, 2008;Weiss & Amorose, 2005) the athletic competence subscale (6 items; = 0.71) was used to assess children's perceptions of their athletic ability and their ability to learn sports skills while the global self-worth scale (6 items; = 0.80) was used to measure children's general perceptions of their self. Answering categories for all 12 items consist of a four-choice structured alternative format.…”
Section: Self-perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPPC is a highly reliable (internal consistency reliability of 0.71 ≤ r ≤ 0.91 for the different subscales) and valid instrument to assess different dimensions of self-perception among third-till eighth-grade pupils (aged 8-13 years, Harter, 2012). Similar to previous studies (e.g., Barnett et al, 2008;Weiss & Amorose, 2005) the athletic competence subscale (6 items; = 0.71) was used to assess children's perceptions of their athletic ability and their ability to learn sports skills while the global self-worth scale (6 items; = 0.80) was used to measure children's general perceptions of their self. Answering categories for all 12 items consist of a four-choice structured alternative format.…”
Section: Self-perceptionmentioning
confidence: 99%
“…Such an approach describes the associations between these variables (Magnusson, 1988) and thus provides an overall picture of the average relationship between actual and perceived motor competence (e.g., Barnett, Morgan, van Beurden, & Beard, 2008;Khodaverdi, Bahram, Khalaji, & Kazemnejad, 2013). However, a variable-centred approach does not indicate whether, and to what extent, some children have divergent levels of actual and perceived motor competence.…”
Section: Introductionmentioning
confidence: 99%
“…In the initial phases of motor development, children's MC involves the mastery of fundamental motor skills that are the foundations for the mastery of specialized motor skills. It has been reported that physical activity, 3,4 cardiorespiratory fitness, 5,6 physical fitness, 7 and perceived physical competence, 8,9 have positive effects and associations with MC, as well as an inverse association with weight status 10 in children and adolescents. This has provided emerging evidence to the theoretical model proposed by Stodden and colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…As has been pointed out by White (1959), who was the first to introduce the concept of competence into psychology, since competence is one of the fundamental elements of intrinsic motivation, we can now acknowledge the fact that sports competence is negatively correlated to stress intensity. Barnett et al (2008) also argued that developing a high perceived sports competence through object control in childhood is important for both boys and girls in determining adolescent physical activity participation and fitness. Thus, it can be inferred that sports competence is also related to a child's growth.…”
Section: Discussionmentioning
confidence: 99%